Male Feminists Promote Gender Equality in Islamic Moderation Perspective - Maghfur Ahmad; Siti Mumun Muniroh; Umi Mahmudah (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
This study aimed to analyze the relationship between the role of men in supporting the feminist movement and moderate Islamic teachings among college students in Indonesia. This study used a quantitative approach by distributing questionnaires to 625 respondents who were randomly selected. The independent variable used, namely religious moderation, was measured using four indicators: a sense of nationalism (X1), tolerance (X2), anti-violence (X3), and accommodative attitudes towards local culture (X4). This study examined multiple linear regression analysis to test whether the four problems in Islamic moderation were related to student attitudes towards male involvement in feminism. The results suggested that these four independent variables have a positive and significant effect on student attitudes towards the active role of men in supporting the gender equality movement. Furthermore, an accommodative attitude towards the local culture and a sense of nationalism were known to have the greatest and smallest effects, namely 0.28 and 0.15 respectively. These results indicate that moderate Muslims tend to have a greater acceptance of male feminists. Then, the results also indicated that Muslim students who practised moderate Islamic teachings had realized the importance of male involvement in feminism.